2016
DOI: 10.33844/ijol.2016.60188
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between workers’ remittances, unemployment, labor migration and economic growth in Pakistan

Abstract: This study examines the relationship between workers' remittances and economic growth along with labor migration in Pakistan. The study also investigates the relationship between workers' remittances and unemployment and captures the interaction between unemployment and economic growth. Annual time series data from 1975 to 2010 is used for analysis. Following this, Johansen and Juselius' (1990) co-integration technique and recursive simultaneous equations model have been applied for analysis. Multivariate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…This can be as a result of remittances spent on consumption purposes and not revenue-yielding investments. This has been corroborated in the literature (Adeagbo and Ayandibu, 2014; Asad et al , 2016; Lim and Simmons, 2015). Our findings do not, therefore, conform to the proposition of Cohen (2005).…”
Section: Empirical Results and Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This can be as a result of remittances spent on consumption purposes and not revenue-yielding investments. This has been corroborated in the literature (Adeagbo and Ayandibu, 2014; Asad et al , 2016; Lim and Simmons, 2015). Our findings do not, therefore, conform to the proposition of Cohen (2005).…”
Section: Empirical Results and Discussionsupporting
confidence: 81%
“…Contrarily, Meyer and Shera (2017) found a positive impact of remittances on economic growth with the impact increasing at higher levels of remittance compared to the Gross Domestic Product in a panel study conducted in six developing countries. Similar to findings by Tabassum et al (2017) and Mago (2018), Asad et al (2016) confirmed a long-run relationship between workers’ remittances and economic growth and a uni-directional causality from workers’ remittances to economic growth. Furthermore, the study found a uni-directional causality from unemployment to labor migration.…”
Section: Literature Reviewsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of a dynamic generalized method of moments (GMM) model found that there is a positive relationship between foreign direct investment (FDI) and real GDP growth, but only for low-income African countries, not the middle-income countries. Meanwhile, Asad et al (2016) also examine a study about workers' remittances and economic growth along with labor migration in Pakistan. Using multivariate and bivariate co-integration approach, the results show that there is long-run relationship between workers' remittances and economic growth in Pakistan.…”
Section: Economic and Tourism Factors Affecting The Real Gross Regionmentioning
confidence: 99%
“…These studies investigate the relationship of FDI, DI and employment to real GDP. Based on these studies, the present study will add a different variable, namely tourist, as it is not used in previous studies by Alemu and Lee (2015), Asad et al (2016) and the others. The reason for using the tourist as a variable is because the Special Region of Yogyakata (DIY) is the second main destination for tourists, both domestic and foreign-tourists, after Bali island.…”
Section: Economic and Tourism Factors Affecting The Real Gross Regionmentioning
confidence: 99%